COORDINATION IN DIFFERENTIATED AGRI-FOOD SYSTEMS: A STUDY OF ORGANIC DAIRY SYSTEM IN PARANA STATE (Gestão & Regionalidade, 2018)
The aim of this paper is to analyze the coordination of a differentiated agri-food system (DAS) for organic and agro ecological milk in Paraná, Brazil, discussing how its arrangements favor coordination and value adding for farmers. Results showed two distinct subsystems: in one of them, the organic and agro ecological values disappear downstream, and product is sold as conventional, which deconstruct the DAS. Despite the efforts for horizontal arrangements, sequential interdependence prevails. In the other, reciprocal interdependence prevails, since value is carried along the chain, until final consumer. There is an alignment in goals and value adding among agents along the chain. We conclude that actions and policies for value adding and differentiation in agri-food systems need to come together with proposals for chain coordination, to assure the transmission of value downstream, especially when considering chains with intermediaries between farmers and consumers. Keywords: Dairy chain; agro ecological production; differentiation; organizational arrangements; transaction; participative certification.